METODOLOGI FIKIH KEINDONESIAAN - Ramadhan, M. Rizki Syahrul; Arifin, Syamsul; Huda, Miftahul (Ahkam: Jurnal Hukum Islam, 2021)
This paper aims to formulate a methodological pattern for Indonesian fiqh, which is a method for developing Indonesian Islamic law and giving an appreciation of Indonesian traditions. It is important to formulate this pattern in order to establish a methodological direction or starting point in establishing effective Islamic law in Indonesia and accordance with the socio-cultural conditions of the community. Several previous studies have contributed in establishing this methodological direction, but are not yet comprehensive. Through the study of comparative texts that analyzed using an Islamic legal philosophy approach to the thoughts of Hasbi Ash-Shiddieqy, Hazairin, and Abdurrahman Wahid, this paper concludes that the Indonesian fiqh methodology departs from the spirit to utilize fiqh so that it can be applied in Indonesian society mediated by local customs. To utilize the fiqh, the technical methodologies are various, but the pattern based on the fiqh methodology has a few things in common, that are utilizing "disagreed" legal sources, especially 'urf and istislah, using a meaning approach rather than just a lafaz approach, and applying ijtihad istiṣlāhī supported by bayani and qiyasi. This methodological pattern can be used to unify the various offers of Indonesian fiqh methodologies which in the future can be referred in formulating Islamic law in Indonesia.